PENGARUH KEPUASAN PELANGGAN TERHADAP MINAT BELI ULANG PRODUK SOMETHINC - Clarisa Salsabila; Taufan Umbara; Retno Setyorini (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This study is motivated by the phenomenon of a shift in customer interest in reference on beauty products, which initially prefer to use beauty products from internasional brand, recently preferring to use local beauty products from Indonesia. This study aims to determine what dimensions of customer satisfaction have an effect on repurchase interest in Somethinc’s products.The method used is quantitative research with descriptive type. Multiple linear regression analysis was used as a data analysis technique. The sampling technique used is non-probability sampling with purposive sampling method. This study managed to collect 300 respondents.The descriptive analysis that has been successfully summarized states that product quality, service quality, and repurchase interest are in the good category. Meanwhile, the variables of emotion and ease are included in the very good category. This study also concludes that both simultaneously and partially customer satisfaction has a significant effect on repurchase interestsby 64.2%. The remaining 35.8% is influenced by other variables not examined and explained by this study.